Effect of Covid-19 Lockdown on Perceived Stress Scale in Medical Students - Pranjali Parikshit Muley1 , Parikshit Ashok Muley2 , Komal Ajay Meshram3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Stress is defined as the physiological and psychological state which could overburden anindividual’s ability to appropriately respond to it. In India,the corona virus pandemic had created a suddenclosure of educational institute which leads to shift of conventional classes to virtual classes because ofwhich the medical students were in a stage of dilemma. The present study aimed to assess perceived stressduring the COVID 19 lockdown, among the medical students.Aim and Objectives: To assess the perceived stress of medical students in regard to corona pandemiclockdown.Materials and Method: A cross-sectional online survey study was done on 300 medical students whoseperceived stress were assessed using an online questionnaire. The stress test was done with the help ofPerceived Stress Scale (PSS) which has got 14 items.Results: In 300 medical students (151- boys and 149 girls), the mean perceived stress score was observed as27.60. In boys the PSS score was found to be 27.85 and in girls it was 27.52. When the score were comparedwith the mean validated score the students were having moderate amount of stress (p value < 0.05).Conclusion: The present study concluded that the medical students perceived the moderate level of stress.The study thus concludes that lockdown has affected the psychological well being of medical students.